An Investigation of Intrinsic Elements and Moral Value in The Paddington Film - Khalidin Yusuf; Chairina Nasir; Masrizal Mahmud (English Education Journal, 2022)
Film has become a more modern means of human’s life depiction than novel or any other written literary work because of its ability to present in audio-visual form. One of the film’s essential elements is intrinsic, the elements that interlink and build the film itself. This research centres on the intrinsic elements in The Paddington (2014) film using a structural approach. Moral value is also being discussed in this research using a separated theory by Linda and Eyre (1997). This research is contributing to the richness of current literary work research while simultaneously giving a support to upcoming and ongoing studies. This research analysed the data using descriptive qualitative method developed by Miles and Huberman (2013). Prior to this, the data had been collected using Creswell’s (2012) note-taking technique. The finding of this research discovered five intrinsic elements and twelve moral values in this film. While the intrinsic elements consist of theme, plot, character and characterization, setting, and point of view. More than 10 classifications of moral values were recorded in this study.